Short-term Changes After Corticosteroid Injections Into the Normal Tendons of Rabbits: A Controlled Randomized Study - Dinhane, Kandir Genesio Innocenti [UNESP]; Godoy-Santos, Alexandre Leme [UNESP]; Fabro, Alexandre Todorovic [UNESP]; Moretto, Maria Regina [UNESP]; Depra, Igor [UNESP]; Yoshida, Winston Bonetti [UNESP] (Sage Publications Inc, 2019)
Background: Corticosteroid injections in or around tendons for the treatment of athletic injuries are a common practice among orthopaedic surgeons and are apparently efficacious in the short term, although controversies persist related to local complications. Purpose: This study evaluated short-term (48 hours) biomechanical, biochemical, and histological alterations after a single injection of betamethasone into the normal tendons of rabbits. Study Design: Controlled laboratory study. Methods: A total of 72 New Zealand White rabbits were randomly divided into 2 groups: the test group-in which 36 animals underwent 1 intratendinous injection of betamethasone (1.4 mg / 0.2 mL) in the right calcaneal tendon; the control group-in which the right calcaneal tendon of 36 animals was injected with saline (placebo control group) and the left calcaneal tendon was left untreated for normal standards (normal control). Forty-eight hours later, animals were euthanized and tendons were harvested. Metalloproteinase (MMP1 and MMP2) and interleukin (IL1 and IL6) expression levels, biomechanical resistance (load x elongation parameters), and histomorphometry (hematoxylin and eosin and picrosirius red stains for collagen fibers, tenocytes, and inflammatory cells) were analyzed in the tendons. Results: The test group had a significant reduction in MMP2 expression as compared with the control groups (P = .027). Regarding the other parameters, there were no additional significant differences between the groups. Conclusion: A single injection of corticosteroid into normal calcaneal tendons did not trigger acute local morphological, structural, or biomechanical injuries at 48 hours, but it did promote a significant decrease in MMP2 levels. Additional studies are needed with increased duration of follow-up, various doses, and multiple injections and in tendinopat
Keywords: tendons; corticosteroids; metalloproteinases; histomorphometry